UJI COBA EBOOK BERORIENTASI PROBLEM BASED LEARNING DALAM MATERI CAHAYA DAN ALAT OPTIK UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS - Eggy Wahyu Ristanti; Mohammad Budiyanto (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
The purpose of this research is to describe the features of problem based learning-oriented ebook on light and optical instruments topics to train students’ critical thinking skills. In this research, a pre-experimental method with one group pretest-posttest design was used. This research was conducted at SMPN 1 Pandaan in the academic year of 2020/2021 to 30 eight grade students as participants. The feasibility of problem based learning-oriented ebooks obtained an average validation score of 95% which belongs to very good criteria and an average students’ responses score of 88,67% which belongs to very good criteria. The ability of students to think critically increases after using problem based learning-oriented ebook by the average N-gain score of 0,4197 which belongs to the moderate category. Learning implementation using problem based learning-oriented ebooks gets a very good response from the students by the average score of 87%. The conclusion of this research is that problem based learning-oriented ebooks can be applied to train critical thinking skills of the students.